Prominin-like Regulates Longevity and Glucose Metabolism via Insulin Signaling in Drosophila. - Ryu, T.H.; Yeom, E.; Subramanian, M.; Lee, K.S.; Yu, K. (The journals of gerontology. Series A, Biological sciences and medical sciences, 2019)
CD133, also called Prominin-1, is a biomarker for mammalian stem cells. It is involved in cell growth, development, and tumor biology. However, the function of CD133 at the organismal level has not been investigated. In this study, we found that prominin-like (promL) loss-of-function mutant flies show an extended life span and metabolic defects such as increased circulating carbohydrates, lipid storage, and starvation resistance. The messenger RNA expression levels of Drosophila insulin-like peptides (Dilps) were reduced in loss-of-function promL mutants. Furthermore, the level of phosphorylated AKT, a downstream component of insulin signaling, was lower in promL loss-of-function mutants than in the w- control flies. Importantly, the PromL protein is predominantly expressed in the pars intercerebralis region with insulin-producing cells of the adult brain. When we inhibited promL in insulin-producing cells, these flies showed an extended life span, metabolic defects, and reduced insulin signaling. These results indicate that the promL gene regulates longevity and glucose metabolism by controlling insulin signaling in Drosophila.